Correlation of Polymorphonuclear Cell Burden and Microbial Growth to the Inflammatory Cytokines in Tracheal Aspirates from Ventilated Preterm Infants - Baig, Sophia; Das, Pragnya; Podaralla, Niharika; Evangelista, Alan; Kaur, Ishminder; Bhandari, Vineet (American Journal of Perinatology, 2023)
Objective The significance of the presence of microorganisms and polymorphonuclear cells in the tracheal aspirates (TAs) of ventilated preterm infants is not well known. Our aim was to correlate information about the presence of polymorphonuclear cells with microbial growth and the cytokine milieu in the TAs of infants who have been intubated for >7 days.Study Design TAs were collected from infants who had been intubated for 7 days or longer. Respiratory cultures were performed, and infants were stratified based on the presence and abundance of polymorphonuclear cells and microbial growth. Cytokines were measured in the TAs of each of the respective groups.Results In the 19 infants whose TAs were collected, the presence of at least moderate WBC with presence of microbial growth was positively associated with the presence of interleukin (IL)-10, IL-1β, IL-8, and tumor necrosis factor (TNF)-α. The presence of at least moderate WBC, with or without microbial growth, was correlated positively with the presence of IL-8 and TNF-α.Conclusion There are higher levels of proinflammatory cytokines (especially, IL-10, IL-1β, and TNF-α) in TAs with higher cell counts and presence of microbial growth. The findings suggest that the presence of microbial growth correlated with inflammatory burden and warrant a larger study to see if treatment of microbial growth can ameliorate the inflammatory burden.Key Points
Keywords: cytokines; cell counts; tracheal aspirate cultures; preterm newborn